Makro Ekonomi dan Pengentasan Kemiskinan di Indonesia: Analisis Kemampuan Pertumbuhan Ekonomi dan Indikator Makroekonomi Dalam Pengentasan Kemiskinan di Indonesia - Abi Fadillah (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
Poverty is still a problem in Indonesia's economy. From the colonial period to 75 years of independence, around 27.55 million people still live below the poverty line. This paper tries to examine the impact of Indonesia's macroeconomic variables as proxied by Economic Growth (GDPG), Inward FDI (FDI), Unemployment (UNM), Inflation (IN), Exports (EXP), Imports (IMP) on Indonesia's absolute poverty (POVY) with using annual data from 1979-2020. This study emphasizes economic growth as the primary variable. At the same time, other independent variables are used as control variables. The method in this study uses Autoregressive Distributed Lag (ARDL) and applies bounds testing approach to measuring the long-term relationship between the independent and dependent variables. The cointegration limit test shows that there is long-term cointegration between macroeconomic impacts on poverty in Indonesia. The short-term and long-term ARDL models show that all independent variables have a significant relationship with poverty in Indonesia.